2015
DOI: 10.1039/c4nr05593d
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes for stabilization of nanostructured lipid particles

Abstract: Carbon nanotubes (CNTs) are increasingly studied for innovative biotechnological applications particularly where they are combined with essential biological materials like lipids. Lipids have been used earlier for enhancing the dispersibility of CNTs in aqueous solutions. Here we report a novel application of CNTs for stabilization of internally self-assembled nanostructured lipid particles of 2-5 μm size. Single-walled ( pristine) as well as -OH and -COOH functionalized multi-walled CNTs were employed to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Pickering or a combination of the two mechanisms [17,18]. In case of fullerenes, we found that 25 and 30 g/ml solutions of C60 stabilize the lipid particles into an o/w emulsion; however, lower C60…”
Section: Fullerenes As Stabilizers?mentioning
confidence: 86%
See 4 more Smart Citations
“…Pickering or a combination of the two mechanisms [17,18]. In case of fullerenes, we found that 25 and 30 g/ml solutions of C60 stabilize the lipid particles into an o/w emulsion; however, lower C60…”
Section: Fullerenes As Stabilizers?mentioning
confidence: 86%
“…Emulsions stabilized by solid particles are termed generally as Pickering [32] or Ramsden-Pickering [33] emulsions. Clay platelets [34], food hydrocolloids [35,36] and silica nanoparticles [37] are among such stabilizers, but in our recent work [18] we have employed carbon nanotubes (CNTs) for stabilizing nanostructured lipid particles. Pristine single-walled (SW) CNTs and functionalized multi-walled (MW) CNTs were employed successfully to stabilize internally selfassembled lipid particles [18].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations